Smart-AI: Strengthening Media Advancement And Resourceful Teaching Through Artificial Intelligence – A Capacity Building Program For Teachers - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (LPPM IAIN Sorong, 2025)
Teachers have both possibilities and problems as a result of the rapid growth of artificial intelligence (AI) in education, especially in rural regions where internet literacy is still low. The goal of this community service project, SMART-AI: Strengthening Media Advancement and Resourceful Teaching with Artificial Intelligence, was to improve the ability of SMAN 1 Sirenja instructors to create instructional media that incorporates AI. The program's goal was to improve instructors' confidence, understanding, and proficiency using AI technologies like Magic School AI and Canva AI. Pretest and posttest questionnaires were used as part of a quantitative method to evaluate improvements in teacher competency. SPSS was used for the analysis of data from 25 individuals. Participants' posttest scores significantly improved, according to the results, demonstrating a greater grasp of AI-assisted media creation. Additionally, educators expressed increased enthusiasm and a move toward more creative, student-centered teaching methods. Notwithstanding obstacles including uneven internet connection and disparities in digital skills, the initiative was able to accomplish its goals. In summary, SMART-AI showed the value of consistent AI integration in teacher professional development and made a significant contribution to the preparation of educators for the future.